Delineation of cutter force and cutter wear in different edge configurations of disc cutters – An analysis using discrete element method. (November 2021) - Agrawal, Anil Kumar; Chattopadhyaya, Somnath; Murthy, V.M.S.R.
Highlights: Tunnel boring machines are used for tunnel construction. Disc cutter is primary tool for cutting rocks. The cutters are worn-out due to friction. Cutter edge profile is playing a crucial role. The edge configuration of the cutter changes the life of the cutter. Abstract: Disc cutters are used to cut the rocks in variable load conditions which results in cutter wear and failure. The wear of the cutter plays a vital role in the overall time cycle, efficiency and economics of tunneling projects. It changes the shape of the cutter, influences the cutting efficiency and has a detrimental effect on the annual cost of maintenance, availability, and utilization. In tunneling using TBMs, assessment of wear behavior of the cutters is the most crucial problem to investigate. In this study, interactions between cutter and rock were presented. Cutters with various configurations such as 0, 10, and 20-degree tip angles with different tip widths 7.3 mm and 4.5 mm were used. Cutter penetration varied from 2 to 8 mm in steps of 2 mm. The diameter of cutters are fixed at 6.5 in. and simulation runs against the rock were done for 1.2 m in length. In this simulation, normal force, tangential force, and wear were computed with the help of EDEM software for each configuration. Simulation results show that the tip angle of the cutter and depth of penetration directly affected the cutter wear. A tip angle of 10 0 with 7.3 mm tip width and 6 mm depth of penetration in the rock is the best configuration for obtaining the minimum wear of the cutter. The simulation results are also verified with the previous mathematical models suggested by different researchers. The suggested approach for simulation can help analyze the cutter wear behavior close to real life with given input parameters.